Kompetensi Dan Kinerja Karyawan Bagian Pemasaran - Nuri Herachwati; Atika Dinita S Dinita S (Universitas Airlangga, 2012)
High competence human resources can support employee performance improvement and contribute in determining the company's future. The aim of this research is to examine and analyze the simultaneous and partial effects of competence characteristics consisting of knowledge and skills, self-concept, and the motives and traits on the performance of employees in the marketing department PT. X. The samples in this study were employees of the marketing department PT. X as many as 42 people, technical analysis is a technique used multiple linear regression analysis. The results found that knowledge and skills, self-concept and motive effect traits Employee Performance in the Marketing Department.